A new age of photography: ‘DIY digitization’ in manuscript studies - Wakelin, D (De Gruyter, 2021)
Since c. 2008 many special collections libraries have allowed researchers to take photographs of medieval manuscripts: this article calls such self-service photography ‘DIY digitization’. The article considers some possible effects of this digital tool for research on book history, especially on palaeography, comparing it in particular to the effects of institutionally-led digitization. ‘DIY digitization’ does assist with access to manuscripts, but less easily and with less open data than institutional digitization does. Instead, it allows the researcher’s intellectual agenda to guide the selection of what to photograph. The photographic process thereby becomes part of the process of analysis. Photography by the researcher is therefore limited by subjectivity but it also helps to highlight the role of subjective perspectives in scholarship. It can also balance a breadth or depth of perspective in ways different from institutional digitization. It could in theory foster increased textual scholarship but in practice has fostered attention to the materiality of the text.